Molecular screening and allele identification of Thai banana genotypes for resistance to Fusarium wilt using validated SCAR markers - THANITA BOONSRANGSOM; WERAPAT CHANSONGKRAM; JUTAMAS SAENGJANCHAY; JUANGJUN JUMPATHONG; PONGSANAT PONGCHAROEN; WANWARANG PATHAICHINDACHOTE; Kumrop Ratanasut; KAWEE SUJIPULI (Society for Indonesian Biodiversity, 2024)
Abstract. Boonsrangsom T, Chansongkram W, Saengjanchay J, Jumpathong J, Pongcharoen P, Pathaichindachote W, Ratanasut K, Sujipuli K. 2024. Molecular screening and allele identification of Thai banana genotypes for resistance to Fusarium wilt using validated SCAR markers. Biodiversitas 25: 2590-2601. Fusarium wilt (FW) caused by Fusarium oxysporum f. sp. cubense (Foc), significantly damages commercial banana (Musa spp.) cultivation worldwide, including in Thailand. Cultivating resistant banana genotypes is crucial for managing FW. However, the unique biology of banana plants makes this process challenging and time-consuming. Genetic markers can enhance the efficiency and precision of traditional breeding methods for developing resistant cultivars. This study aimed to screen and identify Fusarium wilt-resistant alleles across six Thai banana genomes. Established sequence-characterized amplified region (SCAR) markers, strongly linked to loci associated with Foc susceptibility or resistance, were used in this investigation. The results revealed significant genetic differences in FW resistance loci among 106 Thai banana genotypes, comprising AA, AAA, AAB, ABB, ABBB, and BB genomes. All genotypes carried at least one FW resistance locus except Musa (AAA) 'Kluai Khieo Pakchong'. Cluster analysis divided the 106 genotypes into two FocR1-resistant and four FocTR4-resistant clusters. No allelic variation was found among M. balbisiana with the BB genomes. Further research is needed to understand the interaction between banana genotypes and Foc strains. These validated SCAR markers will assist in genotype selection for field and greenhouse assessments as part of the Thai banana genetic improvement program.